ANALISIS IMPLEMENTASI AKUNTANSI DIGITAL GUNA PENCATATAN KEUANGAN PADA UMKM - Krisdiyawati Krisdiyawati; Hikmatul Maulidah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
Digitalization of accounting for MSME actors began to use through online applications for financial records. Bookkeeping is easy, and efficient for MSME actors online, introduced the Android-based AKPHB Cash Book Application for accounting records in business financial management. This study aims to analyze the obstacles experienced by MSMEs in applying AKPHB Cash Book financial applications for MSME financial records. The analysis method used is qualitative descriptive by providing reviews through the distribution of questionnaires to research respondents, questions and interviews. The population is MSMEs in the South Tegal area of Tegal City. The accidental sampling technique by chance and deemed suitable has used the AKPHB Cash Book as a data source obtained by 20 respondents. The application of AKPHB Cash Book financial application to MSME actors is still ongoing. It still provides simulation and education. This application has sufficient features in recording accounting for MSME entities, but has not presented financial statements by applicable standards, still applies the basic assumption of cash flow. There are obstacles experienced by MSMEs in this application because it is not attractive. Therefore, the download of this application is still not smooth for the security system of each smartphone. Then, the mindset of MSMEs must be changed about the importance of accounting knowledge in preparing financial statements.